Generalized coefficients of goods quality and satisfying of consumers demand - Safiullin, Lenar; Safiullin, Nail; Ismagilova, Gulnara N. (Applied Studies in Agribusiness and Commerce, 2010)
In process of work the problems are set and solved. There are problems of social welfare research in conditions of nonhomogeneity of objects and subjects of management, of revealing and substantiating insuperable difficulties in rising of social welfare by approaches, worked out before. Also there developed a new direction in implementation of the most important aim of any socially-oriented economy.